Across the sub-Arctics of Canada [electronic resource] : a journey of 3, 200 miles by canoe and snowshoe through the barren lands : including a list of plants collected on the expedition, a vocabulary of Eskimo words, a route map and full classified index - Tyrrell, J. W. (James Williams), 1863-1945 (Toronto : W. Briggs; Montreal : C.W. Coates, 1897)
Includes index. Electronic reproduction. Mode of access: Internet. 44